Pengembangan Perangkat Pembelajaran Matematika dengan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Pada Materi Bangun Ruang Sisi Datar Di Kelas VIII SMP: Pengembangan Perangkat Pembelajaran Matematika dengan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Pada Materi Bangun Ruang Sisi Datar Di Kelas VIII SMP - Rista Rista; Fitriana Yolanda; Dedek Andrian; Aulia Sthephani (Perspektif Pendidikan dan Keguruan, 2022)
This study aims to produce a product of mathematics learning tools in the form of Learning Implementation Plans (RPP) and Student Worksheets (LKPD) with a cooperative learning model of the Two Stay Two Stray (TSTS) type in the material for building flat side spaces for class VIII SMP which has been tested for validity. This research is a development research using the ADDIE development model in the form of Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation). Due to the research being conducted during the Covid-19 pandemic, the researchers limited the development procedure to 3 modified stages, namely Analysis, Design, and Development. The research data collection instruments were in the form of RPP validation sheets and LKPD validation sheets. The data collection technique used is a non-test technique with a data collection instrument in the form of a validation sheet filled out by the validator. The data analysis technique used is descriptive quantitative data analysis. From the results of the analysis of research validation by the three validators, the average validation per-RPP from each validator is 80.88% with a very valid category and for the average validation result per-LKPD from each validator is 84.1% with a very valid category. . Based on the results of the study, it was found that the mathematical learning device with the Two Stay Two Stray (TSTS) type cooperative learning model on the flat-sided building material in class VIII of this junior high school has been tested for validity.